Advanced Neuropsychological Diagnostics Infrastructure (ANDI): A Normative Database Created from Control Datasets - de Vent, Nathalie R.; Agelink van Rentergem, Joost A.; Schmand, Ben A.; Murre, Jaap M. J., ANDI Consortium; Huizenga, Hilde M. (Frontiers in Psychology, 2016)
In the Advanced Neuropsychological Diagnostics Infrastructure (ANDI), datasets of several research groups are combined into a single database, containing scores on neuropsychological tests from healthy participants. For most popular neuropsychological tests the quantity, and range of these data surpasses that of traditional normative data, thereby enabling more accurate neuropsychological assessment. Because of the unique structure of the database, it facilitates normative comparison methods that were not feasible before, in particular those in which entire profiles of scores are evaluated. In this article, we describe the steps that were necessary to combine the separate datasets into a single database. These steps involve matching variables from multiple datasets, removing outlying values, determining the influence of demographic variables, and finding appropriate transformations to normality. Also, a brief description of the current contents of the ANDI database is given.